Peluang gen z untuk menumbuhkan kepedulian terhadap konstitusi - yana, Rusti (Maliki Interdisciplinary Journal, 2025)
Gen Z is a community that was born in 1990-2010, a group of communities that are actuve and have great influence, showing high attention to the constitution and legal issues. However, 40% acknowledged a lack of understanding. Several factors that influences this concern are education, social media and personal experience. Apart from that, Gen Z also has a very close relationship with technology and information and can foster a sense of concern for the constitution by utilizing technology, education and social media. Gen Z has a relationship with the constitution, which aims to regulate the structure, power and has an institutional function and also regulates the relationship between the state and individuals or groups. The relationship between Gen Z and the constitution has a very important relationship because it protects the basic rights and freedoms that are widely practiced by every individual, including us, the Gen Z group. Then, Gen Z also becomes a Digital Native, which is the first time it is present in Indonesia and will replace the Millennial generation or the generation before the Gen Z generation.